DHARMAGITA SEBAGAI TERAPI SENI KEAGAMAAN HINDU UNTUK DOSEN DAN MAHASISWA PADA UNIT KEGIATAN MAHASISWA UNIVERSITAS HINDU INDONESIA - Sari, Ida Ayu Putu; Rudita, I Ketut Gede (WIDYANATYA, 2019)
Dharmagita in the mental spiritual development of religion and increasing understanding of the values of religious teachings. To explore, appreciate and practice the dharmagita teachings within the Hindu University of Indonesia, it is necessary to the role of lecturers and religious leaders by providing direction, guidance, so that students become the next generation of the nation with the mental ideology of Pancasila who have a firm belief (sraddha). and diligently carrying out religious teachings. Mental guidance is needed for students in forming, maintaining and improving the mental condition of religion to foster devotion to God.